Treatment patterns and survival in patients with hepatocellular carcinoma in the Swedish national registry SweLiv. Issue 1 (3rd February 2020) - Henriksson, M.; Björnsson, B.; Sternby Eilard, M.; Lindell, G.; Strömberg, C.; Hemmingsson, O.; Isaksson, B.; Rizell, M.; Sandström, P.
Graphical Abstract: Abstract: Background: Consistent data on clinical features, treatment modalities and long-term survival in patients with hepatocellular carcinoma (HCC) using nationwide quality registers are lacking. This study aimed to describe treatment patterns and survival outcomes in patients diagnosed with HCC using a national maintained database. Methods: Characteristics and treatment patterns in patients diagnosed with HCC and registered in the national register of liver and bile duct tumours (SweLiv) between 2009 and 2016 were reviewed. Overall survival (OS) was estimated using Kaplan–Meier analysis and the log rank test to compare subgroups for clinical features, treatment modalities and outcomes according to the year of treatment. Results: A total of 3376 patients with HCC were registered over 8 years, 246 (7·3 per cent) of whom underwent transplantation. Some 501 (14·8 per cent) and 390 patients (11·6 per cent) had resection and ablation as primary treatment. Transarterial chemoembolization and systemic sorafenib treatment were intended in 476 (14·1 per cent) and 426 patients (12·6 per cent) respectively; the remaining 1337 (39·6 per cent) were registered but referred for best supportive care (BSC). The 5-year survival rate was approximately 75 per cent in the transplantation group. Median OS was 4·6 (i.q.r. 2·0 to not reached) years after resection and 3·1 (2·3–6·7) years following ablation. In patients referred for palliative treatment, median survival was 1·4 (0·8–2·9), 0·5 (0·3–1·2) and 0·3 (0·1–1·0) years for the TACE, sorafenib and BSC groups respectively ( P  < 0·001). Median survival was 0·9 years for the total HCC cohort in 2009–2012, before publication of the Swedish national treatment programme, increasing to 1·4 years in 2013–2016 ( P  < 0·001). Conclusion: The survival outcomes reported were in line with previous results from smaller cohorts. The introduction of national guidelines may have contributed to improved survival among patients with HCC in Sweden.